Hello Scratch! : learn to program by making arcade games - Ford, Gabriel; Ford, Sadie; Ford, Melissa (Manning Publications, 2018)
Hello Scratch! is a how-to book that helps parents and kids work together to learn programming skills by creating new versions of old retro-style arcade games with Scratch. About the Technology Can 8-year-olds write computer programs? You bet they can! In Scratch, young coders use colorful blocks and a rich graphical environment to create programs. They can easily explore ideas like input and output, looping, branching, and conditionals. Scratch is a kid-friendly language created by MIT that is a safe and fun way to begin thinking like a programmer, without the complexity of a traditional programming language. About the Book Hello Scratch! guides young readers through five exciting games to help them take their first steps in programming. They'll experiment with key ideas about how a computer program works and enjoy the satisfaction of immediate success. These carefully designed projects give readers plenty of room to explore by imagining, tinkering, and personalizing as they learn. What's Inside Learn by experimentation Learn to think like a programmer Build five exciting, retro-style games Visualize the organization of a program About the Reader Written for kids 8-14. Perfect for independent learning or working with a parent or teacher. About the Authors Kids know how kids learn. Sadie and Gabriel Ford, 12-year-old twins and a formidable art and coding team, wrote this book with editing help from their mother, author Melissa Ford!